Focus in Words with Truth Values - Göksel, Asli (IBERIA: An International Journal of Theoretical Linguistics, 2010)
This article analyses the prosodic properties of words with truth values in Turkish. These are morphologically complex words that are finite predicates and that can function as declarative sentences. Researchers who have worked on morphologically complex words have generally taken the view that stress occupies a unique position in these words and that this is a consequence of their morpholphonological properties. Here we highlight the fact that the position of stress is in fact variable (an observation originally due to Sebüktekin 1984) and that this variability is a result of the fact that morphologically complex words can be propositional constructions. We narrow down the investigation to propositions that are declarative sentences and suggest that the position of prominence in such words has to do with the information structural properties of the language. The variation in prominence will be argued to be similar to that which occurs in sentences with multiple constituents, and that which reflects the semantic difference between presentational and contrastive focus. The investigation thus brings together two separate lines of research concerning Turkish: the location of stress in morphologically complex words, and the location of pitch in presentational and contrastive focus sentences. The findings will be discussed in the context of their implications for hierarchical views of prosodic prominence and hypotheses concerning focus-alignment.